Pengembangan Bahan Ajar Tematik Digital Berbasis Microsoft Sway untuk Siswa Kelas V di Kecamatan Pucakwangi - Rizka S.A, Muhammad Zamzam; Surachmi, Sri; Setiadi, Gunawan (Jurnal TEKNODIK, 2023)
This research is based on the need for teaching materials that can be used in online learning effectively. The teaching materials needed are the ones that can display various content such as texts, images, sounds, and videos. Students can use the teaching materials anytime and anywhere. The research objectives are: 1) to describe the development design of Microsoft Sway-based digital thematic teaching materials for the 5th grader in Pucakwangi Subdistrict; 2) to describe the feasibility level of Microsoft Sway-based digital thematic teaching materials for the 5th grader in Pucakwangi Sub-district; and 3) to describe the effectiveness of Sway-based digital thematic teaching materials for the 5th grade in Pucakwangi Sub-district. This research is a research and development (R&D) research with ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The result shows that the recapitulation of the media expert validation reaches 95.29% with the category of very feasible, while the result of the content expert recapitulation reaches a percentage of 90.66% with the category of very feasible. The data indicates that Microsoft Sway-based digital thematic teaching materials are feasible to use for learning in Pucakwangi Sub-district. The averages of students’ learning results before using Microsoft Sway-based digital thematic teaching materials in SDN Pucakwangi 01, SDN Pucakwangi 02, and SDN Pucakwangi 03 are 74,54; 73,67; and 74,70. After using Microsoft Sway-based digital thematic teaching materials, their average scores are consecutively 87,73; 88,33; dan 89,70. The results showed a significant difference between learning outcomes before and after using Microsoft Swaybased digital thematic teaching materials in elementary schools in the sub-district of Pucakwangi.